2014
DOI: 10.1111/clr.12342
|View full text |Cite
|
Sign up to set email alerts
|

All‐ceramic restoration of zirconia two‐piece implants – a randomized controlled clinical trial

Abstract: After 24 months, success rates of the two-piece ceramic implants showed no significant difference compared to control two-piece titanium implants. The bonded zirconia implant abutment connection appears to be capable with clinical application over the observed period. However, further control measurements need to confirm the presented data.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

6
148
0
6

Year Published

2015
2015
2021
2021

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 90 publications
(160 citation statements)
references
References 29 publications
6
148
0
6
Order By: Relevance
“…10 In a clinical study it was reported that it could be eliminated by the adhesive abutment fixation of the zirconia two-piece implant system. 30 Similarly in this report; radiographic outcomes were clinically acceptable. In our study, one-piece and twopiece zirconia implants revealed similar marginal bone loss and no microgaps at implant abutment connections that could provide marginal bone preservation.…”
Section: Figuresupporting
confidence: 68%
“…10 In a clinical study it was reported that it could be eliminated by the adhesive abutment fixation of the zirconia two-piece implant system. 30 Similarly in this report; radiographic outcomes were clinically acceptable. In our study, one-piece and twopiece zirconia implants revealed similar marginal bone loss and no microgaps at implant abutment connections that could provide marginal bone preservation.…”
Section: Figuresupporting
confidence: 68%
“…Of the included studies, six solely addressed single tooth replacements (Cannizzaro et al 2010;Gahlert et al 2015;Grassi et al 2015;Kohal et al 2012;Payer et al 2013;Payer et al 2015), whereas only one study solely considered multiple lost teeth, rehabilitated with 3-unit fixed dental prostheses (Kohal et al 2013). Finally, two studies included both indication types (Jung et al 2015;Spies et al 2015a) and were, therefore, split in two independent cohorts according to the type of restoration (SC or FDP) and analyzed separately.…”
Section: Type Of Restorationsmentioning
confidence: 99%
“…Six of these studies described the immediate temporization of the implants with provisional acrylic restorations (Cannizzaro et al 2010;Grassi et al 2015;Jung et al 2015;Kohal et al 2012;Kohal et al 2013;Spies et al 2015a). In the seventh study (Payer et al 2015), the implants were immediately restored with all-ceramic CAD/CAM provisionals without occlusal contacts and after a healing period of 4 months, the implants were restored with all-ceramic crowns. Finally, in two of the included studies a delayedtemporization concept was preferred.…”
Section: Implant Temporizationmentioning
confidence: 99%
“…Bu konu ile ilgili çalışmaların çoğu olgu sunumu şeklindedir. [84][85][86] Günümüzde henüz rutin muayenehane pratiğinde kullanılmasa da, ilerleyen yıllarda zirkonyum implantların özellikle ön bölge estetik olgularda uygulanması öngörülmektedir.…”
Section: Zirkonyum ġMplantlarunclassified